2001
DOI: 10.1002/ijc.1541
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to p53 in human colorectal tumors: A prospective study of 1,209 patients

Abstract: p53 Antibodies (p53-Abs) have been detected in the serum of a proportion of colorectal cancer (CRC) patients. It is not yet known at which stage during colorectal tumor progression p53-Abs appear in the serum. The utility of these antibodies as markers for CRC prognosis remains to be clarified. Using a quantitative enzyme-linked immunosorbent assay, we analyzed serum samples from 998 CRC patients and from 211 patients with polyp. Levels of p53-Abs were defined as negative (<10 U/L), low (10 -76 U/L) and high (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
37
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 31 publications
11
37
0
4
Order By: Relevance
“…In the present study, several factors, including depth of tumor invasion, lymph node metastasis, stage and CEA, were found to be significantly associated with positive Ap53Ab expression. The association between elevated Ap53Ab and lymph node metastasis was consistent with previous data from an Asian population (4,5,7). In gastric cancer, an elevated Ap53Ab level tended to be associated with lymph node metastasis (21), but positive Ap53Ab expression was not found to be correlated with lymph node metastasis in esophageal squamous cell carcinoma (22).…”
Section: Ap53ab Expression N (%) -----------------------------------supporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, several factors, including depth of tumor invasion, lymph node metastasis, stage and CEA, were found to be significantly associated with positive Ap53Ab expression. The association between elevated Ap53Ab and lymph node metastasis was consistent with previous data from an Asian population (4,5,7). In gastric cancer, an elevated Ap53Ab level tended to be associated with lymph node metastasis (21), but positive Ap53Ab expression was not found to be correlated with lymph node metastasis in esophageal squamous cell carcinoma (22).…”
Section: Ap53ab Expression N (%) -----------------------------------supporting
confidence: 89%
“…Mutations of the TP53 gene, which were detected in half of CRC cases (6), were strongly associated with carcinogenesis. The accumulation of mutated-TP53 protein induces the synthesis of Ap53Ab, depending on the condition of the host immune system (7).…”
Section: Introductionmentioning
confidence: 99%
“…Autoantibodies observed in some tumors may be due to large tumor masses and necrosis exposing a large amount of autoantigen to the immune system. Alternatively, as suggested for p53, in which mutations have been found to be associated with more aggressive tumors and poorer prognosis of breast cancer, the mutated p53 tends to have a much longer half-life than the wild-type p53, leading to accumulation of the protein and anti-p53 Ab production (70,71). In contrast, the anti-actin Abs observed in MCB are probably a result of increased tumor cell apoptosis; thus, these Abs serve as a marker of a beneficial biologic process.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, particular interest in such correlations has focused on anti-53 autoantibodies, where some studies observed a correlation between poor prognosis and increased levels of anti-53 autoantibodies (70,71), although these results could not always be confirmed by others (72). It may, therefore, seem surprising that the favorable prognosis of MCB correlates with anti-actin autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Lechpammer et al (2004) in a series of 220 colorectal cancer patients detected p53-Ab mainly in Dukes' B and C stages. Moreover, Tang et al (2001), in a large study of 998 colorectal patients demonstrated that the presence of p53-Ab correlates with tumour progression in colorectal carcinogenesis and an increase with advanced node metastasis. However, in these studies, both colon and rectal cancers were analysed as a single entity, whereas our work was focalised only on rectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%